OFFSET
0,3
COMMENTS
More generally, if g.f. A(x) satisfies: m^n-b^n = Sum_{k=0..n} [x^k]A(x)^n, then A(x) also satisfies: (m+z)^n - (b+z)^n + z^n = Sum_{k=0..n} [x^k](A(x)+z*x)^n for all z and A(x)=(1+(m-1)*x+sqrt(1+2*(m-2*b-1)*x+(m^2-2*m+4*b+1)*x^2))/2.
FORMULA
EXAMPLE
From the table of powers of A(x) (A100226), we see that
3^n-1 = Sum of coefficients [x^0] through [x^n] in A(x)^n:
A^1=[1,1],2,0,-4,0,16,0,-80,...
A^2=[1,2,5],4,-4,-8,16,32,-80,...
A^3=[1,3,9,13],6,-12,-4,48,0,...
A^4=[1,4,14,28,33],8,-24,16,80,...
A^5=[1,5,20,50,85,81],10,-40,60,..
A^6=[1,6,27,80,171,246,197],12,-60,...
PROG
(PARI) a(n)=if(n==0, 1, (3^n-1-sum(k=0, n, polcoeff(sum(j=0, min(k, n-1), a(j)*x^j)^n+x*O(x^k), k)))/n)
(PARI) a(n)=if(n==0, 1, if(n==1, 1, if(n==2, 2, -8*(n-3)*a(n-2)/n)))
(PARI) a(n)=polcoeff((1+2*x+sqrt(1+8*x^2+x^2*O(x^n)))/2, n)
CROSSREFS
KEYWORD
sign
AUTHOR
Paul D. Hanna, Nov 28 2004
STATUS
approved